Feto maternal outcomes with mullerian anomalies - Kohli, Swati; Sharma, Arti; Gupta, Swati; Panwar, Neha; Agarwal, Aditi; Singh, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Congenital anomalies of female reproductive tract may involve the uterus, cervix, or vagina arise from defect in development of Mullerian ducts during fetal life. In mullerian anomalies various types of uterine anomalies are common. Many cases with Mullerian anomalies remain unidentified especially if patient is asymptomatic. They are often associated with obstetric complications like malpresentation, PPROM and preterm delivery. Hence we are presenting a case series to summarize the fetomaternal outcomes with mullerian anomalies.